Geologia, Petrografia e Litogeoquímica dos Gnaisses Porto Alegre, RS, Brasil: Implicações Geotectônicas - PHILIPP, RUY PAULO; DE CAMPOS, ROBERTO SACKS (Pesquisas em Geociências, 2004)
<!– .p text-align: justify; –> The Porto Alegre gneiss is a unit composed of granodioritic to monzogranitic gneisses, with subordinate tonalitic and dioritic rocks. The unit represents the basement intruded by several granitic plutons of Neoproterozoic age. The gneisses show an elongate form of NE-SW direction, and constitute a roof pendant. They have composite banding, which results of injection of dioritic and tonalitic melts, followed by a regional metamorphic event of medium to high grade. Three deformational phases are registered in the gneisses, the latest has a mylonitic nature. Their geochemical features are of medium to high-K, slightly peraluminous granodiorites of calc-alkaline affinity. Comparing the Porto Alegre gneisses with metagranitoids of Pinheiro Machado complex, there are several differences, such as the lower values of Al2O3, Na2O and Sr, and higher values of FeO, MgO, MnO and Rb in the former. These differences indicate that there is no correlation between the Porto Alegre gneisses and Pinheiro Machado complex.